Induction of experimental ulcerative colitis by Fusobacterium varium isolated from colonic mucosa of patients with ulcerative colitis. Issue 1 (1st January 2003) - Ohkusa, T; Okayasu, I; Ogihara, T; Morita, K; Ogawa, M; Sato, N
Abstract : Background: Bacteria are implicated in certain forms of model chronic colitis but the identity and role of bacteria in human ulcerative colitis (UC) are uncertain. Aims: To isolate pathogenic bacteria from inflamed mucosa of patients with UC, to examine whether the bacteria have a toxin to Vero cells, and to determine whether the toxin induces UC-like lesions in animals. Methods: Bacteria were isolated from UC patients and supernatants from cultures were filtered and tested for cytotoxicity to Vero cells. Bacterial cells producing the cytotoxic supernatants were examined by polymerase chain reaction for verotoxin genes. Culture supernatants of cytotoxic strains were examined by high performance liquid chromatography for organic acid concentrations. Mice were given enemas containing organic acid at the mean concentration in the supernatants of cytotoxic strains to ascertain whether colonic lesions appear in UC. Results: Only supernatants from cultures of Fusobacterium varium killed Vero cells. Bacterial cells lacked verotoxin genes. Bacterial culture supernatants contained high concentrations of n -butyric acid and the mean concentration (32 mmol/l) was cytotoxic to Vero cells. Twenty four hours after mice were given enemas containing either butyric acid or F varium culture supernatants, colonic ulcers with crypt abscesses, inflammatory cell infiltration, and apoptotic changes were observed. Conclusions: Butyric acid in culture supernatants from cultures of F varium caused UC-like lesions in mice. This study indicates that F varium may be one of the elusive pathogenic factors in UC.